Estructura textual, macroestructura semántica y superestructura formal de la noticia. - Bueno Lajusticia, Mª Rosario (Estudios sobre el Mensaje Periodístico, 2000)
This paper discusses the different levels of structures of news reports in the press. This news discourse analysis has been carried out taking into account some dimensions of news structures. Firstly, the grammatical style of media texts displays linguistic, grammatical and syntactic structures, such as neologisms, nominalisations, sentence complexity, use of pas 239 M.ª Rosario Bueno Lajusticia Estructura textual, macroestructura semántica y superestructura formal... sive constructions, etc. Style may also signal personal and social factors of the communication context. Secondly, the textual structure of the news that allows us to analyse categories, headlines and leads. Thirdly, the semantic macrostructure by means of which we see the news as a semantic unit with grammatical and lexical cohesion. It organises the content of the text globally and states the most relevant information of the news report. Finally, the formal superstructure that maintains a scheme consisting of six conventional categories: summary, setting, complication, resolution, evaluation and prediction.